Education program for adolescent girl anemia to improve adherence to iron supplementation in remote areas - Sri Yanniarti; Epti Yorita; Rialike Burhan; Erika Yulita Ichwan; Tengku Sri Wahyuni (Malahayati International Journal of Nursing and Health Science, 2024)
Background: One factor influencing the health behavior of teenagers is their level of knowledge. Utilizing applications or digital media in health education can deliver information in a more engaging and easily understandable way for teenagers. This approach helps enhance their understanding of health issues like anemia. Digital interactions enable teenagers to access more detailed knowledge and follow information more effectively. Purpose: To increase the attitudes and behavior of teenagers towards the regular consumption of iron tablets and the prevention of anemia. Method: A quasi-experimental design with a post-test-only control group approach was conducted in the Enggano Island area, North Bengkulu Regency, from January to October 2023. The research examined the relationship between compliance with iron tablet consumption (independent variable) and outcomes such as menstruation duration, age of menarche, and nutritional status (dependent variables). Using purposive sampling, 70 participants were selected and divided into two groups: 35 in the treatment group and 35 in the control group, based on specific inclusion and exclusion criteria. Data analysis included univariate tests to assess the frequency distribution of participant characteristics, followed by bivariate analysis using Wilcoxon, Paired T-Test, Mann-Whitney, Independent Sample T-Test, and MANCOVA. Results: The MANCOVA test results demonstrated that the Chatting Mira education intervention significantly influenced adolescents' knowledge, behavior, compliance with consuming iron supplement tablets, and Hb levels. This was supported by a p-value of 0.000, which was below the α threshold of 0.05, indicating statistical significance at a 95% confidence level. Conclusion: The Chatting Mira education intervention effectively influences teenagers' attitudes and behaviors toward iron tablet consumption and anemia prevention. By utilizing peer-led education and structured activities, this program raises awareness, fosters healthy habits, and encourages adherence to iron supplementation, ultimately reducing the risk of anemia in adolescents.